Endocannabinoid signalling modulates susceptibility to traumatic stress exposure - Rebecca J. Bluett (Nature Portfolio, 2017)
Understanding inter-individual differences in stress-susceptibility could lead to novel treatments and preventative strategies for stress-related pathologies. Here the authors provide evidence that increased endocannabinoid signalling is a resilience factor that buffers against adverse consequences of stress.